2013
DOI: 10.1007/s00464-013-2804-z
|View full text |Cite
|
Sign up to set email alerts
|

Sedation methods can determine performance of endoscopic submucosal dissection in patients with gastric neoplasia

Abstract: Sedation with CPIA can improve ESD performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…Our findings were consistent with those of many past reports. However, aspiration pneumonia was more frequent in our study (11.2% of patients) than that reported in previous studies [8,16,17,18]. For instance, Akasaka et al [8] reported that aspiration pneumonia after ESD occurred in 1.6% of patients.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our findings were consistent with those of many past reports. However, aspiration pneumonia was more frequent in our study (11.2% of patients) than that reported in previous studies [8,16,17,18]. For instance, Akasaka et al [8] reported that aspiration pneumonia after ESD occurred in 1.6% of patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Recently, Park et al [18] reported that sedation with continuous propofol infusion during ESD was higher than that with intermittent midazolam injection, with or without propofol in en bloc resection and complete resection. Conversely, aspiration pneumonia was more frequent in the group receiving continuous propofol infusion than in the group receiving intermittent midazolam injection.…”
Section: Discussionmentioning
confidence: 99%
“…Another key factor for success in this study may have been the participation of an anesthesiologist in all of the procedures because a previous report indicated that sedation administered by an anesthesiologist improved the en bloc resection rate and reduced the procedure time. 45 A large ESD series has reported SM fibrosis in 20% of the cases with mild F1 and severe F2 in 62% and 38% of those cases, respectively. 29 Similarly, our study revealed SM fibrosis in 24% of the cases with F2 cases accounting for 10 (77%) of the total number of 13 SM fibrosis cases probably due to aggressive or bite-on-bite preoperative biopsy 44 as well as the inclusion of 2 local recurrence cases.…”
Section: Discussionmentioning
confidence: 98%
“…Although ESD is generally accepted as a safe treatment, it carries some risks for elderly patients with comorbidities because of the long procedure time (with deep sedation) and procedure-related complications [24][25][26][27][28]. Therefore, in considering the indications for ESD in elderly patients, we must keep in mind their general condition, including the severity of comorbidities and PS score.…”
Section: Discussionmentioning
confidence: 99%